PHOTORECEPTOR INNER SEGMENT MORPHOLOGY IN BEST VITELLIFORM MACULAR DYSTROPHY. Issue 4 (April 2017) - Scoles, Drew; Sulai, Yusufu N.; Cooper, Robert F.; Higgins, Brian P.; Johnson, Ryan D.; Carroll, Joseph; Dubra, Alfredo; Stepien, Kimberly E.
Abstract : Purpose: To characterize outer retina structure in best vitelliform macular dystrophy (BVMD) and to determine the effect of macular lesions on overlying and adjacent photoreceptors. Methods: Five individuals with BVMD were followed prospectively with spectral domain optical coherence tomography and confocal and nonconfocal split-detector adaptive optics scanning light ophthalmoscopy (AOSLO). The AOSLO cone photoreceptor mosaic images were obtained within and around retinal lesions. Cone density was measured inside and outside lesions. In 2 subjects, densities were compared with published measurements acquired ∼2.5 years before. One subject was imaged 3 times over a 5-month period. Results: The AOSLO imaging demonstrated that photoreceptor morphology within BVMD retinal lesions was highly variable depending on the disease stage, with photoreceptor structure present even in advanced disease. The AOSLO imaging was repeatable even in severe disease over short-time and long-time intervals. Photoreceptor density was normal in retinal areas immediately adjacent to lesions and stable over ∼2.5 years. Mobile disk-like structures possibly representing subretinal macrophages were also observed. Conclusion: Combined confocal and nonconfocal split-detector AOSLO imaging reveals substantial variability within clinical lesions in all stages of BVMD. Longitudinal cellular photoreceptor imaging could prove a powerful tool for understanding disease progression and monitoring emerging therapeutic treatment response in inherited degenerations such as BVMD. Abstract : Supplemental Digital Content is Available in the Text.Outer retinal cellular structure in best vitelliform macular dystrophy was assessed using novel adaptive optics retinal imaging, revealing that photoreceptor morphology is highly variable depending on the stage of disease. Photoreceptor structure is still present even at advanced stages of disease, and longitudinal assessment shows that the photoreceptor mosaic is not static.